Development of Rat Meat Detection Using Mt-atp6 Rattus norvegicus Gene Genetic Marker - Maria Sihotang*; Sophian, Alfi; Purba, Maria; Wilasti, Yulin (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2022)
An empirical test using the real-time PCR method to detect food contamination with rat meat (Rattus norvegicus) was conducted. The aims of this study was to provide information on new genetic markers that can be used to detect rat DNA. Detection of rat DNA in meatballs using the genetic marker of the Mt-atp6 (mitochondrial encoded ATP synthase membrane subunit 6) Rattus norvegicus gene was carried out using meatballs containing rat meat. Primers and probes were designed using Primer3Plus and then analyzed for in silico specificity using Primer-BLAST and Nucleotide-BLAST. Forward primer (5'-ACACCA AAAGGACGAACCTG-3'), reverse primer (5'- AGAATTACGGCTCCT GCTCA-3'), and probe (5'-[VIC]-TTCTAGGGCTTCTTCCCCAT-[QSY]-3') with a target size of 161 bp, were successfully designed. The results of empirical validation with laboratory experiments showed that the primer and probe pair can detect Rattus norvegicus specifically. Keywords: rat; Rattus norvegicus; detection; Mt-atp6; real-time PCR *Corresponding author: Tel.: (+62) 81343090080 E-mail: maria.arieni@pom.go.id